PENGARUH FASILITAS PERPUSTAKAAN, KINERJA PUSTAKAWAN DAN KUALITAS INFORMASI TERHADAP KEPUASAN MAHASISWA DALAM MENGGUNAKAN PERPUSTAKAAN POLITEKNIK NEGERI BATAM - Adhitomo Wirawan; Risfandi Risfandi (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2018)
This study aims to determine the influence of library facilities, librarian performance, and quality of information on user satisfaction (students). The respondents of this research are Batam State Polytechnic students. Data collection techniques used questionnaires and documentation. Test the research instrument by using the validity and reliability analysis. Data analysis method used in this research is descriptive analysis and multiple linear regression analysis. This analysis tool is used to know how far library facilities (X1), librarian performance (X2), information quality (X3), to student satisfaction (Y). Partial research results indicate that library facility variables, librarian performance and information quality have positive and significant influence